IL-10/STAT3/SOCS3 Axis Is Involved in the Anti-inflammatory Effect of Benznidazole - Cevey, Ágata C.; Penas, Federico N.; Alba Soto, Catalina D.; Mirkin, Gerardo A.; Goren, Nora B. (Frontiers in Immunology, 2019)
Anti-parasitic treatment for Chagas disease mainly relies on benznidazole, which is virtually the only drug available in the market. Besides its anti-parasitic effects, benznidazole has anti-inflammatory properties. In this work we studied the mechanisms involved in the latter, demonstrating the participation of the IL-10/STAT3/SOCS3 pathway. To achieve this goal, the anti-inflammatory properties of benznidazole were studied using an in vitro model of cardiomyocyte primary culture stimulated with LPS. LPS increased both SOCS3 expression and STAT3 phosphorylation. The addition of benznidazole increased their expression even further. Specific inhibition of STAT3 precluded this effect, suggesting a role for STAT3 in the increase of SOCS3 expression induced by benznidazole. To assess the participation of SOCS3 in the anti-inflammatory effect of benznidazole, we accomplished specific knock-down of SOCS3 with siRNA. Silencing of SOCS3 in cardiomyocytes precluded the inhibitory effects of benznidazole on TNF-α, IL-6, iNOS expression and NO release. Moreover, in the absence of SOCS3, benznidazole could neither prevent IKK phosphorylation nor IκBα degradation, supporting the notion that SOCS3 is required for the benznidazole-mediated inhibition of the NF-κB pathway. Previously, we demonstrated that IL-10 increases the expression of SOCS3 in cultured cardiomyocytes. Here, we found that benznidazole shows a trend to increased IL-10 expression. To evaluate whether benznidazole increased SOCS3 in an IL-10-dependent manner, cardiomyocytes from IL-10 knockout mice were pre-treated with benznidazole and stimulated with LPS. Benznidazole neither inhibited NO release nor avoid IKK phosphorylation or IκBα degradation, showing that IL-10 is required for benznidazole-mediated inhibition of NF-κB. Moreover, exogenous addition of IL-10 to IL-10 knock- out cardiomyocytes restored the inhibitory effect of benznidazole on NO release. The results reported herein show, for the first time, that the IL-10/STAT3/SOCS3 axis is involved in the anti-inflammatory effects of benznidazole. These findings may add up to new therapeutic strategies for chronic Chagas disease given its inflammatory nature.